The ultimate guide to building a Google Cloud foundation : a one-on-one tutorial with one of Google's top trainers - Haggerty, Patrick (Packt Publishing, Limited, 2022)
Follow Google's own ten-step plan to construct a secure, reliable, and extensible foundation for all your Google Cloud base infrastructural needs Key Features Build your foundation in Google Cloud with this clearly laid out, step-by-step guide Get expert advice from one of Google's top trainers Learn to build flexibility and security into your Google Cloud presence from the ground up Book Description From data ingestion and storage, through data processing and data analytics, to application hosting and even machine learning, whatever your IT infrastructural need, there's a good chance that Google Cloud has a service that can help. But instant, self-serve access to a virtually limitless pool of IT resources has its drawbacks. More and more organizations are running into cost overruns, security problems, and simple "why is this not working?" headaches. This book has been written by one of Google's top trainers as a tutorial on how to create your infrastructural foundation in Google Cloud the right way. By following Google's ten-step checklist and Google's security blueprint, you will learn how to set up your initial identity provider and create an organization. Further on, you will configure your users and groups, enable administrative access, and set up billing. Next, you will create a resource hierarchy, configure and control access, and enable a cloud network. Later chapters will guide you through configuring monitoring and logging, adding additional security measures, and enabling a support plan with Google. By the end of this book, you will have an understanding of what it takes to leverage Terraform for properly building a Google Cloud foundational layer that engenders security, flexibility, and extensibility from the ground up. What you will learn Create an organizational resource hierarchy in Google Cloud Configure user access, permissions, and key Google Cloud Platform (GCP) security groups Construct well thought out, scalable, and secure virtual networks Stay informed about the latest logging and monitoring best practices Leverage Terraform infrastructure as code automation to eliminate toil Limit access with IAM policy bindings and organizational policies Implement Google's secure foundation blueprint Who this book is for This book is for anyone looking to implement a secure foundational layer in Google Cloud, including cloud engineers, DevOps engineers, cloud security practitioners, developers, infrastructural management personnel, and other technical leads. A basic understanding of what the cloud is and how it works, as well as a strong desire to build out Google Cloud infrastructure the right way will help you make the most of this book. Knowledge of working in the terminal window from the command line will be beneficial